(untitled) (Archeomatica, 2019)
The project of teleimmersive Archaeology is supported by the Center for Information Technology Research in the Interest of Society (CITRISI) of the Univeristy of Berkeley. This is the first system created worlwide which opened new prospects of changes in the field of archeology. The Ciberarcheology is a new field of research aimed to simulation and investigation of the past.